Observational study of endoluminal mural thrombotic apposition in popliteal artery aneurysm stenting and its relationship with stent-graft geometrical features - Spinella, Giovanni; Conti, Michele; Magliocco, Marco; Pisa, Fabio Riccardo; Finotello, Alice; Pulze, Martina; Pratesi, Giovanni; Cittadini, Giuseppe; Salsano, Giancarlo; Pane, Bianca (Frontiers in Cardiovascular Medicine, 2023)
Introduction. The development of intra-stent thrombosis is one of the mechanisms related to medium-long term failure of endovascular treatment of popliteal artery aneurysm. The present study aims to investigate possible links between the development of endoluminal mural thrombotic apposition in the stented zone (EMTS) with both geometrical features of stent-graft(s) and time of follow-up.Methods. Patients with popliteal artery aneurysm who underwent endovascular treatment were recruited during the follow-up period. Segmentation of computed tomography angiography scan was performed to detect femoro-popliteal artery lumen, leg bones, EMTS, and stent-graft(s). The following parameters were assessed: number, diameter, and length of stent-graft(s); shape, volume, and length of thrombotic apposition within the stent(s). The spiral shape of the thrombotic apposition was evaluated as well.Results. Eighteen male patients were recruited in the study; EMTS was observed in thirteen of them (72%) during the follow-up analysis. An average of 1.8±0.79 stents-grafts were implanted per patient with a median diameter and length of 6.2(1.9) mm and 125(50) mm, respectively. The percentage of the stent length where EMTS is present was on average 42.1% (IQR: 42.4%) with a mean volume of 206.8 mm 3 . A positive correlation was found between length and volume of EMTS (R-squared=0.71, p<0.01). Moreover, EMTS has a helical shape in 8/13 patients whereof 4/5 with counter-clockwise rotation with stent-grafts in the left leg, and 3/3 with clockwise direction treated in the right leg. Higher frequency of EMTS in patients with longer follow-up and higher risk factors is observed, as well.Conclusions. EMTS is observed in most of the cases under analysis especially for medium-long term follow-up. The pattern of such EMTS follows a helical shape having a direction that depends on the leg side. Our results suggest a close surveillance of popliteal aneurysm stenting by follow-up exams to control the onset and progression of EMTS.